Sexual records: the documentation of sexuality and gender - Olivera, Luis Hernandez; Serra, LLuis Esteve Casellas (Tábula, 2018)
We usually face sex from a genital perspective. Most of us interpret it as circumscribed to the sex act and everything related to it. From an academic point of view this perception has been equally limited to the study of its organic status and its use for reproductive purposes. Sex has been an exclusive territory of medicine where the “irregular” is interpreted as a pathology that should be treated and cured by therapies more or less violent in order to eliminate hose sexual behaviors.